Mathematical Yin-Yang

Calculus Level 4

If 1 x = 2 π 0 e a 2 x d α \displaystyle \frac { 1 }{ \sqrt { x } } =\frac { 2 }{ \sqrt { \pi } } \int _{ 0 }^{ \infty }{ e^{ -a^2x }d\alpha } for α > 0 \alpha>0 , evaluate 0 cos x d x x 0 sin x d x x \large \int _{ 0 }^{ \infty }{ \frac {\cos{x} \ dx }{\sqrt{x} } } -\int _{ 0 }^{ \infty }{ \frac{\sin{x} \ dx}{\sqrt{x}} }


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First Last
Jun 5, 2017

Using a general Gaussian 0 x b e a x n d x = Γ ( 1 + b n ) a 1 + b n n (sub x = a x n and use gamma function definition) \displaystyle\int_0^\infty x^be^{-ax^n}dx=\frac{\Gamma(\frac{1+b}{n})}{a^{\frac{1+b}{n}}n}\quad\text{(sub }x=ax^n\text{ and use gamma function definition)}

I = 0 cos x x sin x x d x = 0 x 1 2 e i x + e i x 2 x 1 2 e i x e i x 2 i d x = Γ ( 1 2 ) ( 1 i + 1 i 2 1 i 1 i 2 i ) = \displaystyle I = \int_0^\infty \frac{\cos{x}}{\sqrt{x}}-\frac{\sin{x}}{\sqrt{x}}dx = \int_0^\infty x^\frac{-1}{2}\frac{e^{ix}+e^{-ix}}{2}-x^\frac{-1}{2}\frac{e^{ix}-e^{-ix}}{2i}dx=\Gamma(\frac1{2})(\frac{\frac1{\sqrt{-i}}+\frac1{\sqrt{i}}}{2}-\frac{\frac1{\sqrt{-i}}-\frac1{\sqrt{i}}}{2i})=

Γ ( 1 2 ) ( 1 2 1 2 ) = 0 \displaystyle\Gamma(\frac1{2})(\frac1{\sqrt{2}}-\frac1{\sqrt{2}}) = \boxed{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...